Alternative Solution to Sand Blanket in Vertical Drain - Mohd Nor, Zatul Iffah (Universiti Teknologi PETRONAS, 2008)
Construction industry in Malaysia had a brief sand shortage problem in the year 1996, and as sand becoming increasingly expensive over the years, and the unavailability of clean sand at site can hinder the construction process, alternative material is needed to replace the sand application in the vertical drain system. The report explains briefly on what constitutes a soft soil; its properties and characteristic as well as problems arise from the construction on soft ground. Concept on vertical drain is illustrated to further understand how vertical drain accelerates consolidation in soft soils, different types of vertical drains, and specifically on the prefabricated vertical drain (PVD) and the components of the vertical drains system. The possible use of geocomposite drain i.e Stripdrain™ as an alternative material to replace the sand blanket as the drainage layer in the vertical drain system is studied. Experimental values of the discharge capacity and settlement rate of soil for both drainage systems are included in this report and comparisons were made. The Stripdrain1111 system was found to provide better drainage inthe vertical drain system.